1992
DOI: 10.1159/000247478
|View full text |Cite
|
Sign up to set email alerts
|

Acitretin as Cancer Chemoprophylaxis in a Renal Transplant Recipient

Abstract: The use of acitretin in a renal transplant recipient who had been treated for several premalignant and malignant skin lesions is the subject of this case report. During the treatment period no new dysplastic lesions developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 4 publications
1
13
0
1
Order By: Relevance
“…Experience with oral retinoids in renal transplant recipients has been limited because of theoretical immunopotentiating effects of the drug and concerns regarding graft rejection 5 . Two small uncontrolled studies using etretinate 6 , 7 and an anecdotal report of a single patient treated with acitretin 8 suggest a preventative effect on NMSC development in renal transplant recipients with no adverse effects on graft function. A more recent double‐blind, placebo controlled study using acitretin administered over 6 months showed a significant reduction in the number of new NMSC in the retinoid treated group 9 .…”
mentioning
confidence: 99%
“…Experience with oral retinoids in renal transplant recipients has been limited because of theoretical immunopotentiating effects of the drug and concerns regarding graft rejection 5 . Two small uncontrolled studies using etretinate 6 , 7 and an anecdotal report of a single patient treated with acitretin 8 suggest a preventative effect on NMSC development in renal transplant recipients with no adverse effects on graft function. A more recent double‐blind, placebo controlled study using acitretin administered over 6 months showed a significant reduction in the number of new NMSC in the retinoid treated group 9 .…”
mentioning
confidence: 99%
“…This results in a wide variety of infectious prob lems and in an increased incidence of malignancies. The frequency of developing malignancies is 100 times higher than in the control population and lies between 1.6 and 5.6% [14]. The number of tumors in the cyclosporinetreated group was significantly higher than in the group of patients with a conventional immunosuppression.…”
Section: Discussionmentioning
confidence: 81%
“…Eight studies document the use of acitretin at doses ranging from 0.2 to 0.5 mg/kg per day and from 10 to 50 mg/day in 132 patients 65–72 . Harwood and colleagues conducted a retrospective study on 28 OTRs treated with low‐dose retinoids for 1 to 16 years (27 treated with acitretin, 1 with etretinate) 72 .…”
Section: Retinoids In Otrsmentioning
confidence: 99%